2020
DOI: 10.1097/tp.0000000000003507
|View full text |Cite
|
Sign up to set email alerts
|

HLA and AB0 Polymorphisms May Influence SARS-CoV-2 Infection and COVID-19 Severity

Abstract: Background. SARS-CoV-2 infection is heterogeneous in clinical presentation and disease evolution. To investigate whether immune response to the virus can be influenced by genetic factors, we compared HLA and AB0 frequencies in organ transplant recipients and waitlisted patients according to presence or absence of SARS-CoV-2 infection. Methods.A retrospective analysis was performed on an Italian cohort composed by transplanted and waitlisted patients in a January 2002 to March 2020 time frame. Data from this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 28 publications
7
91
2
1
Order By: Relevance
“…Several studies have examined the HLA antigenic diversity and potential susceptibility to severe SARS‐CoV‐2 infections [45–47]. This is an important consideration, as individuals who express HLA class I and/or class II molecules that have poor affinity for SARS‐CoV‐2 peptides are likely to be more prone to severe infections and develop poor or non‐sterilizing immunity after vaccination.…”
Section: Implications Of Human Leukocyte Antigenic (Hla) Diversity and Susceptibility To Sars‐cov‐2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the HLA antigenic diversity and potential susceptibility to severe SARS‐CoV‐2 infections [45–47]. This is an important consideration, as individuals who express HLA class I and/or class II molecules that have poor affinity for SARS‐CoV‐2 peptides are likely to be more prone to severe infections and develop poor or non‐sterilizing immunity after vaccination.…”
Section: Implications Of Human Leukocyte Antigenic (Hla) Diversity and Susceptibility To Sars‐cov‐2 Infectionmentioning
confidence: 99%
“…In an interesting paper by Amoroso et al . [47], in an Italian transplant population, the investigators found that HLA‐DRB1*O8 showed no peptide binding to SARS‐CoV‐2 peptides and, more importantly, was associated with increased mortality from SARS‐CoV‐2 [odds ratio (OR) = 2·9, 95% confidence interval (CI) = 1·15–7·21, P = 0·023]. The authors conclude that HLA antigen typing can identify individuals at higher risk for infection with SARS‐CoV‐2.…”
Section: Implications Of Human Leukocyte Antigenic (Hla) Diversity and Susceptibility To Sars‐cov‐2 Infectionmentioning
confidence: 99%
“…It has been previously shown that specific HLA alleles were more common in patients infected with COVID-19 as compared to healthy individuals (e.g. HLA-DRB1* 15:01, HLA-DQB1* 06:02, HLA-DRB1*08, HLA-C*04:01) and it was extrapolated that these alleles may predispose to infection 31,[41][42][43] . It is not surprising that some of these alleles differed from ours, as we identified a genetic predictor specifically for severe clinical course amongst patients with COVID-19, while other groups compared healthy vs diseased.…”
Section: Ds3mentioning
confidence: 99%
“…The immunogenetic background of the host, such as HLA diversity, is well known to play an essential role in determining host responses to emerging infectious diseases such as TB (6), HBV (7-10), HCV (11,12), HIV (13,14), SARS-CoV-1 (15)(16)(17)(18)(19) and SARS-CoV-2 (20)(21)(22). In cases of viral infection, viruses have successfully breached the early layers of the innate defense system (early nonspecific responses) such as fever, phagocytosis and inflammation.…”
Section: Introductionmentioning
confidence: 99%